National Security and the Threat of Arms Proliferation: A Case Study of Nigeria’s Niger Delta - ABOYADE, Ariyo Sunday (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2023)
The implications of the proliferation of small arms and light weapons (SALWs) on Nigeria’s national security are mammoth posing an existential threat to the state. The crisis that engulfed the Niger Delta, especially from the 1990s onward was exacerbated by the copious availability of SALWs in the region. Adopting a historical approach, this paper examines the strategic implications of the proliferation of Small Arms and Light Weapons (SALWs) in the delta region for Nigeria’s national security. The Social Conflict Theory and Human Needs Theory are adopted as theoretical frameworks for the study. Based on its findings, the paper concludes that the Nigerian governments have not been entirely sincere to the process of curbing the scourge of arms proliferation in the country. It recommends effective regulations and border control as an efficient measure to address the illicit trade in SALWs and its proliferation and asserts that if the problems of proliferation in the Niger Delta region and other parts of Nigeria are not addressed frontally, the non-state armed and warlords operating in the regions will undermine the state and plunge it into a dangerous conflict zone where the gangs will rule at the expense of legitimate authority, development, security and progress of all.